2015
DOI: 10.1371/journal.pone.0134118
|View full text |Cite
|
Sign up to set email alerts
|

Baseline C-Reactive Protein Levels and Life Prognosis in Parkinson Disease

Abstract: BackgroundC-reactive protein (CRP) is a biomarker of inflammation, and high levels of CRP correlate with vascular death. Chronic inflammation is considered to be involved in neurodegeneration, although there is no evidence linking it with the process of neurodegenerative diseases.ObjectiveTo determine the role of baseline CRP levels in the prognosis of patients with Parkinson disease (PD).MethodsA cohort of 313 patients with a mean age of 69.1 and mean PD duration of 7.9 years was retrospectively followed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 45 publications
1
41
1
Order By: Relevance
“…Umemura et al conducted a retrospective study and found out that the CRP level was associated with the motor function during 5 different follow-up periods in PD patients; and reported that this relationship was independent from drug usage and gender 21 . Another retrospective study by same research group revealed that the CRP levels were independent from the disease duration and the incidence of the diseaserelated mortality 22 . Song et al found CRP levels are higher in PD patients 23 .…”
Section: Discussionmentioning
confidence: 95%
“…Umemura et al conducted a retrospective study and found out that the CRP level was associated with the motor function during 5 different follow-up periods in PD patients; and reported that this relationship was independent from drug usage and gender 21 . Another retrospective study by same research group revealed that the CRP levels were independent from the disease duration and the incidence of the diseaserelated mortality 22 . Song et al found CRP levels are higher in PD patients 23 .…”
Section: Discussionmentioning
confidence: 95%
“…44 C-reactive protein is known to mediate the link between glucose and uric acid 45 and has been shown to be a predictor of life expectancy and death in PD. 46 Further important predictors for faster motor progression were neurofilament light chains in CSF. The neurofilament medium, heavy, and light subunits contribute to the cytoskeleton including axial and dendritic branching and growth.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis, patients with Parkinson disease and elevated CRP levels at baseline had a significantly shortened survival compared with those with normal CRP levels. 46 Moreover, CRP has been associated with severity of functional impairment in other neuromuscular disorders. In particular, in patients with Duchenne muscular dystrophy, high levels of CRP (mean, 3.94 md/dL) were associated with poor functional impairment and obesity.…”
Section: Discussionmentioning
confidence: 99%